Pelatihan Tata Kelola Keuangan Dan Sistem Pembukuan Untuk UMKM Mitra BUMD Kota Bontang - Anisa Kusumawardani; Alan Smith Purba; Emayanti Christina Hutabarat; Nur Alfiah Rezkiyanti; Rizka Dwi Jayanti; Diah Fitri Harseno (CV. Multi Kreasi Media, 2025)
A training programme was implemented for MSMEs (Micro, Small, and Medium Enterprises) in Bontang City, with a focus on financial governance and bookkeeping systems. These enterprises, in their capacity as partners of BUMD (Regional-Owned Enterprises), were the beneficiaries of this initiative. The objective of the programme was twofold: firstly, to enhance business performance and sustainability; and secondly, to address deficiencies in financial governance and the absence of transparency, which was primarily attributable to conventional or non-existent transaction recording. The objective of this activity is to furnish MSMEs with a comprehension of the principles of sound financial administration and the capacity to implement a bookkeeping system in accordance with SAK EMKM. The implementation method involves the following: first, the identification of in-depth needs; second, the design of a comprehensive curriculum (comprising basic, advanced and specialised modules); and third, the development of concise, compact and relevant teaching materials with specific case studies. The training approach emphasises interaction and practical application through discussions, simulations, and case studies, delivered by experienced instructors. The training programme was found to have yielded substantial improvements in the participants' comprehension of fundamental financial concepts, the accounting cycle, and their practical skills in recording transactions and preparing basic financial statements. The participants' responses indicated a high level of satisfaction with the relevance of the materials and the effectiveness of the delivery methods. The initial impact is evident in the heightened awareness of the significance of record accuracy and sound financial governance, which serves as the basis for internal and external system enhancements. The potential long-term impacts of the initiative include enhanced accuracy of BUMD financial reports, operational efficiency, increased PAD contribution, and improved access to financing for partner MSMEs. The challenges that must be anticipated are limited resources, technology adoption, and the need for ongoing mentoring.